Design a prototype of a marine wave power plant (PLTGL) using a recoil starter - Lesnussa, Henny; Farhan, Fauzi; Patiran, Abdul Z.; Rehiara, Adelhard Beni; Sarungallo, Pandung; Rumengan, Yanty (Journal of Innovation Materials, Energy, and Sustainable Engineering, 2023)
As the needs of human life increase, the need for electrical energy will also increase. Currently, fossil energy, which is widely used as fuel for the provision of electrical energy, is running low. In Indonesia, renewable energy sources have not been utilized properly, such as wave energy. This study discussed how to design a prototype of a sea wave power plant. The problem is, how to be able to utilize the energy of sea waves to the maximum. The purpose of this research is to find solutions and designs to utilize recoil starter as a prototype of ocean wave power plants. The methodology used in this study is an experiment in which the prototype made is given a certain treatment and then measurements are made. His data analysis technique is descriptive analysis. Based on the results of measurements and observations, the performance of the tool is not only influenced by the height of the wave, but also the period of arrival of the sea wave and the ballast load of the tool. After measurements were made on the first day of Maruni beach, the prototype could produce an average power of 4.21 watts for an average wave height of 0.35 cm and Maruni beach on the second day could produce an average power of 5.68 watts for an average wave height of 0.4 m. While on the first day Amban beach obtained an average power of 3.29 watts for an average wave height of 0.37 cm and Amban beach on the second day could produce an average power of 14.26 watts for an average wave height of 0.5 m.